Fabrication and Characterisation of Some Metallic Nano/Microstructure Materials by Template Synthesis - Pabla, Raminder Kaur (My University, 2008)
The present study is concerned with the synthesis and characterization of high aspect-ratio, one-dimensional metallic nano/microstructures having lengths of the order of 10 μm and diameter ranging from 800 nm, down to 15 nm. Such materials are of particular interest in the field of microelectronics. For the last few decades, the electronics industry has been achieving miniaturization chiefly by refining the process of photolithography. Current trends indicate that the futuristic electronic devices will be structured on the scale of a few nanometers, which will be many orders of magnitude smaller in comparison to the contemporary devices. In this backdrop, nano/microwires have emerged as among the most interesting structures with potential to find applications in many fields, such as magnetic sensors, high density data storage devices and as electrical interconnects in nano/micro devices. In the present work, electrochemical template synthesis has been used for fabricating the nano/microstructures, wherein the chemically developed pores of a polycarbonate nuclear track filter membrane act as templates, into which the metal is deposited electrochemically. We procured commercially available Nuclepore® membranes of various pore sizes from Whatman®. According to the reviewed literature, high aspect ratio metallic nano/micro wires have many potential applications such as interconnects in electronic devices and as emitters in field emission arrays etc. The nano/micro wires fabricated through template synthesis can be used in different ways, viz. as embedded in the template, as free-standing structures on the substrate, or in a free form suspended in some suitable medium. The study involves electrochemical template synthesis of copper, nickel and chromium nano/microstructures using polycarbonate nuclear track filter as template. The Nuclepore polycarbonate membrane templates employed for the purpose had a thickness of 9 to 11µm with pore density ranging from 107 to 108 cm-2. Pore sizes used ranged from 800nm, down to 15nm. A special-purpose electrochemical cell was designed and fabricated for carrying out the template synthesis. The cell has a modular design and provision for controlling & monitoring various process parameters viz. temperature, stirring, current density etc. Selection of deposition parameters during electrochemical template synthesis plays the key role not only in determining whether the intended nano/microstructures will be successfully fabricated; but also influences their characteristics. An important parameter in electrochemical deposition is the current density (mA/cm2). Through iterative procedure, it was established that a current density of 8 to 10 mA/cm2 gave the most favorable results for deposition in the polycarbonate nuclear track filter membrane. Proper wetting of the membrane with distilled water has been found to have a very favourable influence in the form of simultaneous commencement and uniform growth of microstructures. The characteristics such as morphology and crystallographic structure of the fabricated nano/micro structures were studied by means of scanning electron microscopy, transmission electron microscopy, selected area electron diffraction and X-ray diffraction techniques. Electron and X-ray diffraction studies reveal a BCC crystal lattice for chromium and FCC lattice for copper & nickel nano/microstructures. The fabricated structures are usually textured. In case of copper, this texturing decreases considerably upon increasing the temperature at the time of electrodeposition. For all the three metals, a slight reduction in texturing is observed upon exposure to radiation from UV laser. The photoluminescence spectrum of the fabricated nano/microstructures was recorded by exposing them to pulsed ultraviolet radiation from a nitrogen laser and recording the intensity-time graphs. The studies revealed that copper and chromium did not exhibit any emission when irradiated with ultraviolet laser light. However, the nickel nanostructures exhibited weak photoluminescence, which gave hyperbolic decay curves arising from adsorbed nickel hydroxide. The electrical characterization involved passing current through the fabricated nano/microstructures and obtaining the current-voltage characteristics. All nano/microstructures were found to obey ohm’s law.
P.hD.
Keywords: Nano Wires; Micro Wires; Template Synthesis